Capacity to Use Parking Facilities The Lampung State Polytechnic Joint Lecture Building: Kapasitas Penggunaan Fasilitas Parkir di Gedung Kuliah Bersama Politeknik Negeri Lampung - Titi Ariyanti; Agustina, Resti; Desniati, Emmi (UNIVERSITAS INDO GLOBAL MANDIRI, 2023)
ABSTRACT The increasing number of new student admissions for the 2023/2024 academic year at the Lampung State Polytechnic has an impact for increasing the number of vehicles that will go through the road or park their vehicles in lecture building. The use of the Joint Lecture Building facilities will be used in early 2023 cannot be separate from the available vehicle parking facilities. Reduce public transportation, which causes students, lecturers, Educational Laboratory Institution, technicians, and other employees switching to use private vehicles. The purpose of this study was to find out how much parking capacity is available for users of the Joint Lecture Building. Methods use by conduct on-site surveys, conducting measurements, calculation of PSU for motorcycles and passenger cars. Based on the survey results, three parking locations were obtained. With an area of Location 1 of 1196,184 m2, Location 2 of 3020,028 m2, and an additional Location 3 of 1319,628 m2. From the land area, then calculate the PSU for Passenger Cars 2.5 m x 5 m and PSU for Motorcycles 0.75m x 2 m. The width of the Alley Lane for 1-way Passenger Cars is at least 6 m and 2-way is at least 8 meters, while for motorcycles is 1.6 meters. Results obtained for Location 1 resulted in 57 PSU for Motorcycles and 27 PSU for Passenger Cars. Location 2 produces 672 PSU for Motorcycles and 47 PSU for Passenger Cars. An additional location 3 resulted in 540 PSU Motorcycles. Thus, the total for Motorcycles is 1244 PSU and Passenger Cars is 74 PSU, for a total of 1343 PSU. The area of land used for Location 1 for Motorcycles is 85.5 m2, Passenger Cars is 337.5 m2, and the remaining area of the alley lane width is 773,184 m2. Location 2 for Motorcycles is 1008.00 m2, Passenger Cars is 587.5 m2, and the remaining area of the alley lane width is 1424.528 m2. Location 3 for Motorcycles is 810.00 m2, remaining area of the alley lane width is 509.628 m2. Keywords : Parking, Parking Space Units (PSU), Parking Capacity ABSTRAK Bertambahnya jumlah penerimaan mahasiswa baru tahun ajaran 2023/2024 di Politeknik Negeri Lampung memberikan dampak bertambahnya jumlah kendaraan yang akan melalui jalan maupun memarkirkan kendaraannya di gedung perkuliahan. Pemanfaatan fasilitas Gedung Kuliah Bersama yang mulai digunakan awal tahun 2023 tidak dapat dipisahkan dari fasilitas parkir kendaraan yang tersedia. Berkurangnya transportasi umum, yang menyebabkan mahasiwa, dosen, PLP, teknisi, dan pegawai lainnya beralih mengunakan kendaraan pribadi. Tujuan penelitian ini adalah untuk mengetahui seberapa besar kapasitas parkir yang tersedia untuk pengguna Gedung Kuliah Bersama. Metode yang digunakan dengan melakukan survei di lokasi, melakukan pengukuran, perhitungan SRP untuk sepeda motor dan mobil penumpang. Berdasarkan hasil survei diperoleh 3 lokasi parkir yang tersedia. Dengan luas Lokasi 1 sebesar 1196.184 m2, Lokasi 2 sebesar 3020,028 m2, dan Lokasi 3 tambahan sebesar 1319,628 m2. Dari luas lahan tersebut, kemudian menghitung SRP Mobil Penumpang 2.5m x 5 m dan SRP untuk Sepeda Motor 0.75m x 2 m. Lebar Jalur Gang untuk Mobil Penumpang 1 arah adalah minimal 6 m dan 2 arah minimal 8 meter, sedangkan untuk motor adalah 1.6 meter. Hasil diperoleh untuk Lokasi 1 menghasilkan 57 SRP untuk Sepeda Motor dan 27 SRP untuk Mobil Penumpang. Lokasi 2 menghasilkan 672 SRP untuk Sepeda Motor dan 47 SRP untuk Mobil Penumpang. Lokasi 3 tambahan menghasilkan 540 SRP Sepeda Motor. Maka total untuk Sepeda Motor 1244 SRP dan Mobil Penumpang 74 SRP, dengan total keseluruhan 1343 SRP. Luasan lahan yang digunakan untuk Lokasi 1 untuk Sepeda Motor sebesar 85,5 m2, Mobil Penumpang sebesar 337,5 m2, dan Sisa luas Lebar jalur gang 773,184 m2. Lokasi 2 untuk Sepeda Motor sebesar 1008,00 m2, Mobil Penumpang sebesar 587,5 m2, dan Sisa luas Lebar jalur gang 1424,528 m2. Lokasi 3 untuk Sepeda Motor sebesar 810,00 m2, Sisa luas Lebar jalur gang 509,628 m2. Kata Kunci : Parkir, Satuan Ruang Parkir (SRP), Kapasitas Parkir